Ovarian dynamics and hemodynamics of pubertal fat-tail ewes supplemented moringa seed cake before and after exogenous progesterone synchronization - Abuelmagd, Sabreen M.A.; Ismail, Tayseer I.M.; Abo El-Maaty, Amal M.; Elnady, Ismail A. (Journal of Advanced Veterinary Research, 2025)
To study the effect of supplementation of moringa seed cake on the ovarian dynamics and hemodynamics, hormonal and antioxidant capacity of yearling ewes, native ewes (n=20) were equally divided into control supplemented the basal diet and moringa seed cake (MSC) supplemented orally 7.0g daily for 45 days. After 17 days of starting supplementation, exogenous 45mg progesterone sponges were inserted for a short period (6 days) and each animal was administrated 2.5mg Dinoprost tromethamine on the day of sponge removal. Ultrasound Doppler was conducted and blood samples were collected on the day of sponge insertion (Day -6), sponge removal (Day 0), Days 2, 9, 15, and 21. Results indicated increased dominant follicle diameter and number in ewe-lambs supplemented with MSC on Day 2 (P=0.0007), 9 (P=0.009), and Day 21 (P=0.005)Subordinate follicle diameter of MSC increased on Day -6, 2 (P<0.0001), 9 (P=0.004) and 21 (P=0.012). The follicle’s average circumference, area, and perimeter increased (P<0.0001) in ewe-lambs supplemented with MSC on Days 2, 9, and 21. CL diameter, perimeter, and area of MSC reached the highest (P<0.0001) on Day 15 but those of control reached the maximum diameter (P=0.032) on Day 21. Ovarian color area of MSC increased (P<0.01) on days 0 and 2. The concentrations of total antioxidants, glutathione reduced, catalase, and SOD increased in ewe lambs supplemented MSc. In conclusion, MSC improved follicle and luteal development, ovarian hemodynamics, and response to synchronization using short-term exogenous progesterone. MSC improved the antioxidant capacity and decreased lipid peroxidation during the estrus of ewes.